STI (Science Technology and Innovation ) policy review - Science and Technology Policy Institute (Seoul Science and Technology Policy Institute, 2010)
STI Policy Review is a multidisciplinary journal that shares high-quality, empirical and practical knowledge on science and technology policy in order to further a robust global community of STI policy researchers, policy makers and practitioners. The primary focus of the journal is on STI policy issues in East Asian countries, but the journal also welcomes all papers that have direct and indirect policy implications for East Asian countries. By facilitating exchanges of empirical analyses and discussions on STI policy issues, the journal aims to promote mutual understanding as well as cross-cultural and cross-national learning that contributes to global STI-based development
published Quarterly till 2011, frequency changed 2/ times /year (2012-
Keywords: Technology; TECHNOLOGICAL INNOVATIONS; SCIENCE; PERIODICALS